A study on allelopathy effects of dinoflagellate margalefidinum (cochlodinium) polykrikoides on pyrodinium bahamense - Normawaty Mohammad-Noor; Asilah Al-Has; Sitti Raehanah Muhamad Shaleh; Deny Susanti (International Islamic University Malaysia, 2024)
The dinoflagellate Margalefidinium polykrikoides, a fish killer, is found all over the world and is associated with harmful algal blooms (HABs). In this study, we investigated the allelopathy effects of M. polykrikoides on the growth of toxic dinoflagellate Pyrodinium bahamense. Allelopathy effects of M. polykrikoides were studied using different volumes (10 mL, 20 mL, and 50 mL) of filtrate filtered from M. polykrikoides’s bloom collected from the field and cultured medium. The results showed that P. bahamense was inhibited significantly (p<0.05) in 50 mL cell-free culture filtrate of M. polykrikoides bloom with an inhibition rate of >80%, but not in M. polykrikoides cell-free culture filtrate. In a bialgal, non-contact culture experiment of M. polykrikoides and P. bahamense at three different ratios was also conducted, separated by a 5µm membrane. The observation showed that at a ratio of 1:5 (100 cells mL-1 of M. polykrikoides: 500 cells mL-1 P. bahamense), P. bahamense cell number increased significantly (p<0.05) after Day 4. This study provides useful information on competing with P. bahamense and forming bloom to dominate the area occupied by M. polykrikoides.